2020
DOI: 10.1186/s13007-020-00656-8
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the inoculation of Phytophthora palmivora (Butler) into cacao seedlings under greenhouse conditions

Abstract: Background: The black pod disease affects cacao plantations worldwide; it is caused by the oomycete species of the genus Phytophthora. The resistance of cacao plants to the black pod is commonly evaluated by artificial inoculation of the pathogen and the monitoring of the disease symptoms. However, it is difficult to identify resistant plants because the commonly used methods for the inoculation of the pathogens produce inconsistent results. Therefore, this study aimed to develop an efficient and reliable meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…In contrast, trinitarian materials have been represented as susceptible to BPD disease, as suggest Paulin et al (2008). In this sense, the current study demonstrated that genotype CCN51 behaves as susceptible, consistent with other studies (Ramírez 2016;Delgadillo-Durán et al 2020;de Souza et al 2021). For this reason, the CCN51 clone might be employed as a susceptible control in BPD research in Colombia.…”
Section: Data Analysis Of Artificial Inoculation Methodssupporting
confidence: 90%
“…In contrast, trinitarian materials have been represented as susceptible to BPD disease, as suggest Paulin et al (2008). In this sense, the current study demonstrated that genotype CCN51 behaves as susceptible, consistent with other studies (Ramírez 2016;Delgadillo-Durán et al 2020;de Souza et al 2021). For this reason, the CCN51 clone might be employed as a susceptible control in BPD research in Colombia.…”
Section: Data Analysis Of Artificial Inoculation Methodssupporting
confidence: 90%
“…It is important to note that multiyear agronomic characterization requires standard protocols shared among breeding programs for phenotyping traits, such as yield (e.g., pod index), seed weight, drought, and disease resistance. For example, new available methods can be adapted by different cacao research programs to evaluate yield and disease resistance (Jaimez et al., 2020), resistance to BPR in seedlings (Delgadillo‐Durán et al., 2020), and on detached fruits (Puig et al., 2021). In addition, standard protocols to evaluate cacao quality and flavor are available (ISCQF, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of inoculum and severity of infection perform a crucial role in precise assessment of disease to screen resistant germplasm. Moreover, the method and type as well as concentration of inoculum is important which determines the establishment and severity of infection (Thakare and Gaikwad, 2014;Patil et al, 2017;Sujata et al, 2020;Delgadillo-Durán et al, 2020). This study was intended to compare, identify and develop a reliable artificial inoculation technique including quantification of inoculum for development of web blight rapidly on mungbean at high severity.…”
mentioning
confidence: 99%